The Dynamic Relationship Between Invasive Microvascular Function and Microvascular Injury Indicators, and Their Association With Left Ventricular Function and Infarct Size at 1-Month After Reperfused ST-Segment–Elevation Myocardial Infarction. (28th October 2022) - Demirkiran, Ahmet; Robbers, Lourens F.H.J.; van der Hoeven, Nina W.; Everaars, Henk; Hopman, Luuk H.G.A.; Janssens, Gladys N.; Berkhof, Hans J.; Lemkes, Jorrit S.; van de Bovenkamp, Arno A.; van Leeuwen, Maarten A.H.; Nap, Alexander; van Loon, Ramon B.; et al.
Abstract : Background: The invasive microvascular function indices, coronary flow reserve (CFR) and the index of microcirculatory resistance (IMR), exhibit a dynamic pattern after ST-segment–elevation myocardial infarction. The effects of microvascular injury on the evolution of the microvascular function and the prognostic significance of the evolution of microvascular function are unknown. We investigated the relationship between the temporal changes of CFR and IMR, and cardiovascular magnetic resonance-derived microvascular injury characteristics in reperfused ST-segment–elevation myocardial infarction patients, and their association with 1-month left ventricular ejection fraction and infarct size (IS). Methods: In 109 ST-segment–elevation myocardial infarction patients who underwent angiography for primary percutaneous coronary intervention (PPCI) and at 1-month follow-up, invasive assessment of CFR and IMR were performed in the culprit artery during both procedures. Cardiovascular magnetic resonance was performed 2 to 7 days after PPCI and at 1 month and provided assessment of left ventricular ejection fraction, IS, microvascular obstruction, and intramyocardial hemorrhage. Results: CFR and IMR significantly changed over 1 month (both, P <0.001). The absolute IMR change over 1 month (ΔIMR) showed association with both microvascular obstruction and intramyocardial hemorrhage presence (both, P =0.01). ΔIMR differed between patients with/without microvascular obstruction ( P =0.02) and with/without intramyocardial hemorrhage ( P =0.04) but not ΔCFR for both. ΔIMR demonstrated association with both left ventricular ejection fraction and IS at 1 month ( P <0.001, P =0.001, respectively), but not ΔCFR for both. Receiver-operating characteristics curve analysis of ΔIMR showed a larger area under the curve than post-PPCI CFR and IMR, and ΔCFR to be associated with both 1-month left ventricular ejection fraction >50% and extensive IS (the highest quartile). Conclusions: In reperfused ST-segment–elevation myocardial infarction patients, CFR and IMR significantly improved 1 month after PPCI; the temporal change in IMR is closely related to the presence/absence of microvascular damage and IS. ΔIMR exhibits a stronger association for 1-month functional outcome than post-PPCI CFR, IMR, or ΔCFR.